PERBANDINGAN SIMULASI REKAYASA TRAFFIC QUALITY OF SERVICE (QOS) PADA SOFTWARE DEFINED NETWORK DENGAN MENCARI JALUR TERPENDEK MENGGUNAKAN ALGORITMA YEN DAN FLOYD-WARSHALL - Henokh F Supusepa (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2022)
Internet services and technology are rapidly expanding in terms of complexity, design, management, and operation leading to an increase in the number of connected devices, and the traffic on the network has increased very rapidly in recent years. Also, emerging new service developments and the use of high mobility and server virtualization, cloud computing, and the Internet of Things are being developed resulting in a network architecture that is currently very limited in capabilities. Software Defined Network technology is a new concept in designing, managing, and implementing network architecture by separating the control system from the forward system on network equipment. Software Defined Network allows the network to dynamically adjust the environment to simplify management and increase network scalability through the simple implementation of additional network components and services. Therefore, higher requirements are put forward to improve network performance and eventually network control becomes increasingly complex, inconsistent, and inflexible. Network performance can be affected by many factors, such as network configuration, number of requests, and network management methods